Product orientated sewage sludge composting technologies in the practice of AKSD Ltd. - Hunyadi, Gergely; Bíró, Tibor; Tamás, János; Piskolczi, Miklós (Acta Agraria Debreceniensis, 2008)
In recent years the regulations of the EU unambiguously determine that the biodegradable wastes should be used for biogas production or composting. The direct use of sewage sludge in agriculture is limited by its hazardous microelement content, but it can be used effectively in composting. The limitation parameters can be extinguished with correct compost-mixture and technology variants. The exact determination of the technologies and mixtures result a stable, constant quality product. The compost, as a classified product, is friable structured. The end-product is a homogeneous mould with good water capacity, does not contain any weed seeds and pathogenic organisms. The compost does not have a acidify effect on the soil. It is an effective fertilizer thanks to its macro and microelement content.